A Comparative Study of Electrocautery Versus Cold Scalpel For Skin Incision In Inguinal Hernia Repair - Ansari, Meraj Alam; Mishra, S. M.; Baskota, B. D. (Journal of Nepalgunj Medical College, 2017)
Introduction: Electrocautery has been widely used except for the skin incisions; this is because of the fear of scarring of skin, post operative pain, poor wound healing and wound infection in view of devitalisation of tissues. Although still not very popular, yet the use of diathermy instead of scalpel for making skin incision and underlying tissue dissection is gradually gaining wide acceptance. The purpose of this study was to compare the scalpel incision with electrocautery incision over skin in patients undergoing hernia repair. Aims and Objectives: To compare the skin wound made by the diathermy and scalpel with a view in; intraoperative incision time, post operative pain, requirement of analgesia and the quality of wound healing. Material and Methods: This is hospital based comparative study, undergone elective inguinal hernia repair in the department of general surgery at Nepalgunj medical college teaching hospital, Kohalpur from the period of July 2015 to January 2016. Group A, contained 30 patients who underwent skin incision with scalpel and Group B, also contained 30 patients who underwent skin incision with electrocautery. These groups were compared and statistical analysis using SPSS (version 20) was done and p value 0.05 was taken as significant. Results: Compared with a scalpel incision, cutting diathermy resulted in significantly shorter incision time (p <0.002). The two groups did not differ in relation to post operative pain and the post operative analgesics requirements. The postoperative complications viz, seroma and purulent collections were in both the groups though the hematoma collection was seen more in scalpel skin incision. Conclusion: Skin incision made by cutting diathermy was less time taking and there was no appreciable differences in postoperative pain, the requirements of analgesia and the rate of wound complications like seroma, and purulent collection, though the hematoma was seen more in scalpel skin incision. So the use of diathermy for making skin incision is as safe as the use of scalpel in patients undergoing inguinal hernia repair. JNGMC Vol. 14 No. 1 July 2016, Page: 14-17